Prospects of light sterile neutrino searches in long-baseline neutrino oscillations - Yakefu Reyimuaji; Chun Liu (Journal of High Energy Physics, 2020)
Abstract The neutrino oscillation probabilities in vacuum and matter are discussed, considering the framework of three active and one light sterile neutrinos. We study in detail the rephasing invariants and CP asymmetry observables, and investigate the four-neutrino oscillations in long-baseline neutrino experiments, such as DUNE, NOνA and T2HK. Our results show that the matter effect enhances quite a significantly the oscillation probabilities of electron neutrino and electron antineutrino appearance channels within a certain energy range, while no considerable change arises in the CP asymmetry analysis due to the matter effect. Moreover, separation between the results with and without the sterile neutrino is not so significant and that is also affected by CP-violating phases. Comparing the results for these three experiments, all of them have similar features, nevertheless, sizes and separations of the oscillation probabilities in DUNE are bit larger.